STRATEGI PEMASARAN WISATA MINAT KHUSUS OFFROAD KALI GENDOL DESA SINDUMARTANI KECAMATAN NGEMPLAK KABUPATEN SLEMAN PROVINSI DAERAH ISTIMEWA - Anggraeni M.S Lagalo (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2019)
Tourism marketing is a management process of tourism organization or tourism industry to figure out the tourist who wants to travelling and a potencial tourist to travel by having communication with them, influence theme, their needs, their motivation, to the thing they like or dislike, in the local level, regional level, national level and even international level by prepare object and attraction of tourism so they will do satisfied. This article analized the marketing strategy of special interest tourism, offroad Kali Gendol Desa Sindumartani Ngempak subdistrict, Sleman regency, Province of Daerah Istimewa Yogyakarta. The method of this reseach is descriptive survay. The data collected by observation, documentation and then to strengthen the data by questioners and interview. The result of this research shows that market characteristic to special tourism offroad of Kali Gendol is the extrime sport lovers’ community, natural lovers’ community, social community, researcher, student, photographer community. The main reason adventure activitie, tourists number still not efective. The tourists wish quality travelling, looking for something new and expand their experience. Tourism product that can be package based on the condition found in the field and the analysis consideration of market potencial is track Offroad which consist of three kinds those are; Fun Offroad, Extreme and Tour Offroad.